1997
DOI: 10.1152/ajpgi.1997.273.6.g1246
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of shock-induced gastric damage by a nitric oxide-releasing aspirin derivative: role of neutrophils

Abstract: The gastric damage associated with hemorrhagic shock appears to occur, at least in part, through neutrophil-dependent mechanisms. Nitric oxide (NO)-releasing derivatives of aspirin have been shown to spare the gastrointestinal tract of injury. As NO can inhibit neutrophil adherence, it is possible that such a derivative of aspirin (NCX-4016) would exert inhibitory effects on neutrophil adherence and therefore be capable of protecting the stomach against shock-induced gastric damage. This hypothesis was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 23 publications
7
69
1
3
Order By: Relevance
“…However, mice treated orally with equimolar NCX-4016 demonstrated no evidence of gastric injury, which is consistent with previous reports using NO-releasing aspirin (35,37). Furthermore, unlike aspirin, NCX-4016 treatment did not significantly alter platelet COX-1 activity (Fig.…”
Section: No-releasing Aspirin (Ncx-4016) Attenuates Hc-induced Platelsupporting
confidence: 91%
See 2 more Smart Citations
“…However, mice treated orally with equimolar NCX-4016 demonstrated no evidence of gastric injury, which is consistent with previous reports using NO-releasing aspirin (35,37). Furthermore, unlike aspirin, NCX-4016 treatment did not significantly alter platelet COX-1 activity (Fig.…”
Section: No-releasing Aspirin (Ncx-4016) Attenuates Hc-induced Platelsupporting
confidence: 91%
“…NO-releasing aspirin has been shown to inhibit thrombus formation in rats and mice (24,35) and to attenuate formylmethionine-leucine-phenylalanine-stimulated and colitis-induced leukocyte adhesion in mesenteric rat venules (36,37). The failure of NCX-4016 (60 mg/kg) to inhibit COX-1 activity in our study agrees with reports of higher doses (compared with aspirin) of NO-aspirin derivatives (NCX-4016 and NCX-4215) being required to inhibit platelet COX-1 activity (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug was also found to be devoid of typical toxic effects of COX-1 inhibitors (NSAIDs) on gastric mucosa also following repeated oral administration. This through inhibition of neutrophil adherence to vascular endothelium [3]. In addition, recent results indicated that NCX4016 is a powerful agent in improving the post-ischemic ventricular dysfunction in the rabbit heart [4] and in reducing the infarct size in rat heart induced by ischemia-reperfusion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Part of the protective effect of H 2 S may be related to its ability, like NO [16], to suppress leukocyte adherence to the vascular endothelium [17], a crucial event in the pathogenesis of ischemia-reperfusion injury that contributes to prolonged impairment of tissue perfusion after the ischemic period. The more quickly blood flow can be restored to the mucosa, the less tissue injury will occur.…”
mentioning
confidence: 99%